Re-investigating the effect of individual determinant, external factor and firm characteristics on small firm performance during economic downturn - Lucky, Esuh Ossai-Igwe; Minai, Mohd Sobri (Academic Journals, 2012)
There have been inconsistencies with regard to the different entrepreneurial factors that influenced firm performance, particularly in normal time. However,during economic downturn or turbulence, it is believed and expected that the three major characters (entrepreneur, environment and firm) in the economy that are actively involved in entrepreneurial activities would be badly and negatively affected. Despite this, an empirical study substantiating these arguments seems to be lacking, particularly in the small business and entrepreneurship domain.This therefore suggests that some of the major influential factors of individual determinant, external factor and firm characteristics in entrepreneurial development and small businesses should be re-investigated in line with the current situation in order to see if they remain significant during economic downturn.Based on this, a cross-sectional study was conducted using a questionnaire survey research design, and data were generated from 182 entrepreneurs or owner-managers of small firms in both manufacturing and service industries.The questionnaires were distributed through drop-off and pick procedure of data collection.The findings indicated that the relationship between individual determinants, external factor and firm characteristics, and firm performance remain significant during economic turbulence.